Contrast Expansion Method for Elastic Incompressible Fibrous Composites - Piotr Drygaś; Vladimir Mityushev (Advances in Mathematical Physics)
Contrast parameter expansion of the elastic fields for 2D composites is developed by Schwarz’s method and by the method of functional equations for the case of circular inclusions. A computationally efficient algorithm is described and implemented in symbolic form to compute the local fields in 2D elastic composites and the effective shear modulus for macroscopically isotropic composites. The obtained new analytical formula contains high-order terms in the contrast parameter and explicitly demonstrates dependence on the location of inclusions. As a numerical example, the hexagonal array is considered.